2020
DOI: 10.1080/17461391.2020.1838618
|View full text |Cite
|
Sign up to set email alerts
|

Is it enough to use the traditional approach based on average values for basketball physical performance analysis?

Abstract: Understanding the most demanding scenarios of basketball match-play can optimise training prescription. We established physical demand differences in total distance covered, distance covered at high-speed running, distance covered at highintensity accelerations and decelerations, number of high-speed running actions and number of high-intensity accelerations comparing the traditional average method with the most demanding scenarios based on 1-minute rolling averages. Physical demand parameters were analysed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 43 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…Given this variability in activity duration and playing time, assessing intensity in basketball is necessary when monitoring external load as it is less dependent on duration than measures capturing total load (volume). However, quantifying only average intensity across total games fails to detect passages of higher physical demands known as most demanding scenarios (MDS) (Vázquez-Guerrero & Garcia, 2020). Recent research in basketball demonstrated that when assessing the MDS during different time windows, players are exposed to intensities much greater than the intensities previously reported using game averages Several studies have assessed the physical demands encountered by basketball players across entire games (Russell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Given this variability in activity duration and playing time, assessing intensity in basketball is necessary when monitoring external load as it is less dependent on duration than measures capturing total load (volume). However, quantifying only average intensity across total games fails to detect passages of higher physical demands known as most demanding scenarios (MDS) (Vázquez-Guerrero & Garcia, 2020). Recent research in basketball demonstrated that when assessing the MDS during different time windows, players are exposed to intensities much greater than the intensities previously reported using game averages Several studies have assessed the physical demands encountered by basketball players across entire games (Russell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These findings reinforce the importance of considering specific PD variables for different functions due to the specific insight they each provide. In addition, given that the external PD attained by basketball players is impacted by various factors including schedule congestion (Edwards et al, 2018), player position (Alonso et al, 2020; Vázquez-Guerrero & Garcia, 2020), and game score-line (Vázquez-Guerrero et al, 2020), the impact of individualized playing time should be considered in tandem with these other factors. Another notable finding in our study was the high CV% across PD variables suggesting wide variability in the data obtained across players.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the peak demand (PD), defined as the most intense activity experienced by players for a selected variable across a specified timeframe of interest (Alonso et al, 2020), has been quantified in basketball players using many external variables (e.g., PlayerLoad, distance, accelerations, and decelerations) and time windows (e.g. 30 s, 45 s, 1 min, 5 min, and 10 min) (Alonso et al, 2020; Fox, Conte, et al, 2020; Fox, Salazar, et al, 2020; Vázquez-Guerrero et al, 2020; Vázquez-Guerrero & Garcia, 2020). In this regard, the impact of different factors on the PD attained by players during basketball games has been explored, including the effects of player position (Alonso et al, 2020; Fox, Conte, et al, 2020), game score-line (Vázquez-Guerrero et al, 2020), and game schedule (Pino-Ortega et al, 2019).…”
mentioning
confidence: 99%
“…To the best of the authors´ knowledge, only Vazquez-Guerrero et al 14 have described the most demanding scenarios (in terms of physical demands) during basketball match-play from professional male players. These authors used the same ROLLING approach and locomotive measures that in the current study and hence, direct comparisons with the physical demands found for the training drills in the current study can be made.…”
Section: Discussionmentioning
confidence: 99%
“…This novel approach takes the most relevant (in terms of sport performance) physical demand measures, after having examined the data second by second, and using all of this data to determine rolling average time duration or epochs (e.g., 0-3, 1-4, 2-5 min). This new rolling average time epoch approach (ROLLING) has been recently used to describe the most demanding scenarios of competitive basketball match-play, showing that the activity profile described is much more demanding than that reported in previous studies where traditional average measures have been employed 4,12,14 . The use of this novel ROLLING approach to quantify the most demanding scenarios of the most frequently used basketball drills (such as 5-on-5 scrimmage situations) may provide a more comprehensive estimation of the external workload imposed on players 15 .…”
Section: Introductionmentioning
confidence: 98%